Adsorption using Selective Adsorbents as An Effective Method for Rare Earth Elements Recovery–a Review - Jamilah, Nurul; Cahaya, Adam B; Riswoko, Asep (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
Rare Earth Elements (REEs) are strategically important for the industry, especially in the manufacture of high-technology products and components, such as electric batteries for energy storage, energy conversion, defense and security industry, electric vehicles, components on smartphones, laptops, liquid crystal display, and others. Generally, REEs are processed by liquid-liquid extraction. However, this process is very costly due to the use of chemicals and high operational costs, so the waste has the potential to pollute the environment. Currently, innovative separation/recovery techniques are continuously being developed for effective and environmentally friendly extraction of rare earths. The adsorption method using the optimal adsorbent is one of the most efficient methods for recovering REEs at low concentrations. This method offers several advantages, including high release effectiveness, ease of installation and operation, low maintenance costs, and reduced chemical consumption. This study reviews the mechanism, characterization, and several adsorbents from natural to synthetic materials, especially nanocomposite-based adsorbents for the recovery of rare earths. In addition, the discussion of several parameters that affect the adsorbent. However, the results of several methodological breakthroughs that have been carried out show how much further research is needed